Efektivitas Manajemen Pengelolaan Dana Zakat Dalam Meningkatkan Kesejahteraan Mustahik Di BAZNAS Jakarta - Astuti, Windy Fuji; Kurniawan, Naufal (STAI Publisistik Thawalib Jakarta, 2023)
Indonesia has the potential for zakat as a tool to reduce and improve poverty and people's welfare. The management of zakat funds certainly has a very vital role in the success of achieving the benefit of the people. This study evaluates the effectiveness of the management of the optimal distribution of zakat funds so that it can significantly contribute to poverty reduction and better welfare. This type of research is library research conducted using existing literature on the Indonesian National Zakat Agency by collecting data through a literature review of books, notes, and research reports from previous studies. Data analysis techniques were carried out using inductive techniques consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate: Indonesia's National Zakat Agency has been effective in the management of zakat management, both in planning, organizing, implementing, and supervising.